The secret of the old mill - Dixon, Franklin W. (New York : Grosset & Dunlap, 1990)
Frank and Joe unravel two mysteries, one involving a counterfeiting case and the other concerned with a national security case on which their father is working.
4.8
5-8
Keywords: Counterfeits and counterfeiting -- Juvenile fiction; National security -- Juvenile fiction; Counterfeits and counterfeiting -- Fiction; Mystery and detective stories; National security -- Fiction; Counterfeits and counterfeiting -- Fiction; Mystery fiction; National security -- Fiction; Mystery fiction